2009
DOI: 10.1002/ijc.24148
|View full text |Cite
|
Sign up to set email alerts
|

The clonal evolution of metastases from primary serous epithelial ovarian cancers

Abstract: Several models of evolution from primary cancers to metastases have been proposed; but the most widely accepted is the clonal evolution model proposed for colorectal cancer in which tumors develop by a process of linear clonal evolution driven by the accumulation of somatic genetic alterations. Various other models of cancer progression and metastasis have been proposed, including parallel evolution and the same gene model. The aim of this study was to investigate the evolution of metastases from primary cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 21 publications
5
49
0
Order By: Relevance
“…In addition to the differences noted in recurrences compared with primary specimens, we found that expression of some of the markers (i.e., PGP as well as EGFR, BCRP, RRM1, and TOPO1) also differed in recurrent specimens taken from the same patient at different times during the course of disease. These differences may reflect alterations in gene expression programs that are dependent on the site of the tumor as suggested by genomic profiling studies of primary ovarian and omental lesions (22) or the genotypic divergence observed in multiple metastases derived from matched primary tumors obtained from untreated patients (23). In our study, the recurrences tested were obtained from patients who had received 1 to 5 prior therapies, so it is also possible that the chemotherapy regimen received in the intervening time period either induced/repressed expression of these proteins or selected for a preexisting tumor cell population with an altered expression of that marker.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the differences noted in recurrences compared with primary specimens, we found that expression of some of the markers (i.e., PGP as well as EGFR, BCRP, RRM1, and TOPO1) also differed in recurrent specimens taken from the same patient at different times during the course of disease. These differences may reflect alterations in gene expression programs that are dependent on the site of the tumor as suggested by genomic profiling studies of primary ovarian and omental lesions (22) or the genotypic divergence observed in multiple metastases derived from matched primary tumors obtained from untreated patients (23). In our study, the recurrences tested were obtained from patients who had received 1 to 5 prior therapies, so it is also possible that the chemotherapy regimen received in the intervening time period either induced/repressed expression of these proteins or selected for a preexisting tumor cell population with an altered expression of that marker.…”
Section: Discussionmentioning
confidence: 99%
“…The alternative explanation is that most of the metastatic potential of the ovarian carcinoma cells already exists in the genetic changes present in the primary tumor and, therefore, it depends less on metastasis related selection pressure. This hypothesis was further refined by an elegant study from Khalique et al 95 who evaluated clonal evolution between primary ovarian tumors and their metastasis using parsimony tree analysis, a software usually used to understand the evolution of animal species. They found that all metastases closely resemble the primary tumor and that different cancer clones within the primary tumor can give rise to metastasis.…”
Section: Late Metastasis: Tumors Transforming the Secondary Sitementioning
confidence: 99%
“…Investigations of the transcriptional profile by microchip analysis (23,24), chromosomal constitution after genomic hybridization (25,26), and parsimony tree analysis (27) of paired ovarian carcinomas and their corresponding metastases concluded that tumor cells from both locations exhibited the same pattern of expression. These findings are in agreement with the hypothesis that ovarian cancer metastases are generated by passive transport of tumor cells with ascites.…”
Section: General Issues Of Pathogenesis Of Ovarian Cancermentioning
confidence: 99%